Cardio-Oncology Rehabilitation and Telehealth: Rationale for Future Integration in Supportive Care of Cancer Survivors - Batalik, Ladislav; Filakova, Katerina; Radkovcova, Ivana; Dosbaba, Filip; Winnige, Petr; Vlazna, Daniela; Batalikova, Katerina; Felsoci, Marian; Stefanakis, Marios; Liska, David; Papathanasiou, Jannis; Pokorna, Andrea; et al. (Frontiers in Cardiovascular Medicine, 2022)
The direct toxicity of cancer treatment threatens patients and survivors with an increased risk of cardiovascular disease or adverse functional changes with subsequent progression of cardiovascular complications. An accumulation of cardiovascular risk factors combined with an unhealthy lifestyle has recently become more common in cancer patients and survivors. It has been recommended to integrate a comprehensive cardiac rehabilitation model called cardio-oncology rehabilitation to mitigate cardiovascular risk. Nevertheless, cardiac rehabilitation interventions limit barriers in low utilization, further exacerbated by the restrictions associated with the COVID-19 pandemic. Therefore, it is essential to integrate alternative interventions such as telehealth, which can overcome several barriers. This literature review was designed as a framework for developing and evaluating telehealth interventions and mobile applications for comprehensive cardio-oncology rehabilitation. We identify knowledge gaps and propose strategies to facilitate the development and integration of cardio-oncology rehabilitation telehealth as an alternative approach to the standard of care for cancer patients and survivors. Despite the limited evidence, the pilot results from included studies support the feasibility and acceptability of telehealth and mobile technologies in cardio-oncology rehabilitation. This new area suggests that telehealth interventions are feasible and induce physiological and psychological benefits for cancer patients and survivors. There is an assumption that telehealth interventions and exercise may be an effective future alternative approach in supportive cancer care.